Prevalence of diabetic complications and risk factors among diabetic foot ulcer patients: a retrospective hospital-based study - P., Shanmuga Raju; N., Venkata Ramana; V., Surya Narayana Reddy; S., Bhagya Seela; G., Sachin (International Surgery Journal, 2018)
Background: Diabetic foot ulcer is a painful, demands increased health care utilization, and increases healthcare costs for the patients as well as the health care system. The purpose of this study was to analysis the prevalence of diabetic foot complications and risk factors among diabetic patients at tertiary care Hospital, Karimnagar. Methods: Total 60 sample sizes were included in the study. The study was conducted at General Surgery ward, Chalmeda Anand Rao Institute of Medical Sciences, Karimnagar from July 2017 to June 2018. Demographic, complications and risk factors were recorded, and outcomes were analyzed using SPSS statistics version 21.0. Results: The Mean age of the study group is 50.31±14.26 years. The male to female distribution is 47 (78.3%) and 13 (21.7%) respectively. The mean duration of illness in days is 96.68±289.21, while mean HbA1C is 9.44±9.02. The mean fasting blood sugar and postprandial blood sugar is 159.78±70.01 and 157.78±86.28 which shown no significance difference (p = 0.87). Odds ratio with 95% confidence interval was computed to the level of significant. Conclusions: There was no significant outcome was found in diabetic foot ulcer. Patient with high risk complications need as early detection, foot care education, moderate physical, exercise, fitted foot wear and diabetic diet should be decrease the risk of diabetic foot ulcers.